Novel and classical morbilliviruses: Current knowledge of three divergent morbillivirus groups - Seki, Fumio; Takeda, Makoto (Microbiology and immunology, 2022)
Currently, seven species of morbillivirus have been classified. Six of these species (Measles morbillivirus, Rinderpest morbillivirus, Small ruminant morbillivirus, Canine morbillivirus, Phocine morbillivirus, and Cetacean morbillivirus) are highly infectious and cause serious systemic diseases in humans, livestock, domestic dogs, and wild animals. These species commonly use the host proteins signaling lymphocytic activation molecule (SLAM) and nectin-4 as receptors, and this usage contributes to their virulence. The seventh species (Feline morbillivirus: FeMV) is phylogenetically divergent from the six SLAM-using species. FeMV differs from the SLAM-using morbillivirus group in pathogenicity and infectivity, and is speculated to use non-SLAM receptors. Recently, novel species of morbilliviruses have been discovered in bats, rodents, and domestic pigs. Because the ability to use SLAM and nectin-4 is closely related to the infectivity and pathogenicity of morbilliviruses, investigation of the potential usage of these receptors is useful for estimating infectivity and pathogenicity. The SLAM-binding sites in the receptor-binding protein show high similarity among the SLAM-using morbilliviruses. This feature may help to estimate whether novel morbillivirus species can use SLAM as a receptor. A novel morbillivirus species isolated from wild mice diverged from the classified morbilliviruses in the phylogenetic tree, forming a third group separate from the SLAM-using morbillivirus group and FeMV. This suggests that the novel rodent morbillivirus may exhibit a different risk from the SLAM-using morbillivirus group, and analyses of its viral pathogenicity and infectivity toward humans are warranted.